Stany Graniczne Skręcanych Elementów z Liniowo Zmiennym Ciśnieniem Bocznym - Gambin, W. (Engineering Transactions, 1973)
In the paper is solved the problem of load carrying capacity of a twisted rod of annular cross-section loaded by linearly variable lateral pressure. Two particular cases are considered: that of the ring mounted on a rigid pin and that of the ring clamped within a rigid pipe. The results derived are then generalized to elements having arbitrary annular cross-sections. In the limit case of vanishing lateral pressure, the usual solutions describing the classical problem of torsion of cylindrical shafts are obtained.